Strategic Myopia - Methodological Issues of a Systematic Literature Review - Czakon, Wojciech; Klimas, Patrycja; Kawa, Arkadiusz (Studia Oeconomica Posnaniensia, 2019)
This study outlines three issues typical for the first step in any systematic literature review process: delimitation, selection and abundance. The meaning and consequences of each issue are explained. With the example of a systematic literature review on strategic myopia the process is commented on in detail, and solutions to each of the issues are proposed.